An Experimental Study Using the Statistical Tool D-optimal Design for the Process Optimization to Enhance the Yield of β-galactosidase from Lactobacillus plantarum - Anbalagan, Nivetha; Vaithilingam, Mohanasrinivasan (Indian Journal of Pharmaceutical Education and Research, 2021)
Context: The Novelty of the research is to formulate the probiotic product with low cost submerged fermentation for the mitigation of lactose intolerance. The utilization of substrate enhances the production of β-galactosidase from the potent strain Lactobacillus plantarum by optimizing the media using the response surface methodology tool. This research is expected to result in innovative scientific outcomes leading to the development of lactose-free products cheaply. Aim: The current research is focused on the optimization of cultural conditions using a D-optimal experimental design to enhance the yield of β-galactosidase. Materials and Methods: Interaction of two physical and chemical factors such as lactose 0.5–2%, beef extract 0.5–2%, pH 6–8, and temperature 30–40°C, were studied in 3D interaction. β-galactosidase production was estimated using the hydrolysis of o-Nitrophenyl β-D-galactopyranoside as the substrate. Further, the enzyme was purified by 70% precipitation, fractionated with 50-kDa ultra-filtration, and separated in gel permeation chromatography with the matrix Sephadex-G100. The extracted β-galactosidase from Lactobacillus plantarum has been immobilized in alginate and hardened with calcium chloride for lactose hydrolysis using Glucose oxidase-Peroxidase assay. Results: The molecular sequencing of VITDM15 was confirmed as Lactobacillus plantarum in 16srRNA sequencing. Using the optimized conditions there was a six-fold increase in the yield of β-galactosidase. The purified β-galactosidase from Lactobacillus plantarum KX838907 yielded 31.75% with 67.73 fold and specific activity of 1705IU/mg. The molecular weight of the enzyme was found to be 112kDa at denaturing conditions in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. In GOD-POD assay the glucose dosage increased up to a maximum level of 4.891mg/l in the 4th cycle. Conclusion: Based on the results obtained we claim that this might be the first report on the enhanced yield of β-galactosidase and lactose hydrolysis. Thus novel strain Lactobacillus plantarum KX838907 can be used in the commercial production of β-galactosidase as it is considered safe to use as a probiotic microorganism.
Keywords: β-galactosidase; D-Optimal; SDS-PAGE; Sodium alginate; Lactose hydrolysis